The Influence of Education Level, Training, and Teaching Experience on the Performance of Junior High School Teachers at SMP Negeri 3 Taman - Dewi, Nuning Nurna; Romlah, Dewi Siti (IQTISHADequity jurnal MANAJEMEN, 2024)
This study aims to determine the effect of education, training, and work experience levels on the performance of SMP Negeri 3 Taman teachers. This research is a quantitative study, sampling using saturated sampling (census) where all members of the population are used as a sample of 43 teachers of SMP Negeri 3 Taman. The data collection technique uses questionnaires on the level of education, training, work experience, and teacher performance. Before the questionnaire was used, validity and reliability tests were first carried out with Alpha Cronbach. The analysis method uses multiple linear regression. Hypothesis tests are carried out Normality tests and regression meaningfulness tests. The analysis tool uses IBM SPSS Statistics Version 23. The results showed a significant influence between the independent variable and the dependent variable. The level of education has a positive and significant effect on the performance of SMP Negeri 3 Taman teachers with a significance value (0.000) < a (0.05). There is a significant effect of training on the performance of SMP Negeri 3 Taman teachers with a significance value (0.005) < a (0.05). Work experience has a positive and significant effect on the performance of SMP Negeri 3 Taman teachers with a significance value (0.005) < a (0.05). The level of education, training, and work experience have a significant effect on the performance of SMP Negeri 3 Taman teachers. These findings indicate efforts to improve the level of education, providing relevant training for SMP Negeri 3 Taman teachers in improving the quality of their performance. In addition, teaching experience also needs to be considered and supported so that teachers can continue to develop their skills and knowledge in facing new challenges in the world of education. The implications of the study confirm the importance of the level of education, training, teaching experience in improving teacher performance. Policies and strategies are needed including periodic training, fostering teaching experience to design appropriate programs in improving the overall quality of teacher education.